KOMBINASI PUPUK KANDANG SAPI, ASAM HUMAT DAN MIKORIZA TERHADAP INFEKSI AKAR BERMIKORIZA TANAMAN CABAI DAN KETERSEDIAAN UNSUR HARA TANAH UDIPSAMMENTS - Sukri, M. Zayin; Firgiyanto, Refa; Sari, Vega Kartika; Basuki, Basuki (Politeknik Negeri Lampung., 2019)
This research is an experimental study that aims to examine the combination of cattle manure, humic acid, and mycorrhizae to increase mycorrhizal infections in the roots of chili plants in the Udipsamments soil in Puger District, Jember Regency, which was carried out in May-November 2018. The research design used was a factorial complete randomized block design with 3 factors that were repeated 3 times. The first factor is cattle manure (0 tons / ha, 10 tons / ha, 20 tons / ha), the second factor is humic acid (0 ppm / ha, 200 ppm / ha), and the third factor is mycorrhiza (0 g / plant , 30 g / plant). The results showed that the combination of cattle manure, humic acid, and mycorrhiza inoculants to chili plant roots was able to increase the root mycorrhizal infection of chili plants and increase the nutrients available in the soil by 191.84% for nitrogen and 392.93% for phosphorus.